Causal relationship between iron status and preeclampsia-eclampsia: a Mendelian randomization analysis - Xiaofeng Yang; Jiachun Wei; Lu Sun; Qimei Zhong; Xiaoxuan Zhai; Ya Chen; Shujuan Luo; Chunyan Tang; Lan Wang (Clinical and Experimental Hypertension)
Background Preeclampsia/eclampsia is a severe pregnancy-related disorder associated with hypertension and organ damage. While observational studies have suggested a link between maternal iron status and preeclampsia/eclampsia, the causal relationship remains unclear. The aim of this study was to investigate the genetic causality between iron status and preeclampsia/eclampsia using large-scale genome-wide association study (GWAS) summary data and Mendelian randomization (MR) analysis.Methods Summary data for the GWAS on preeclampsia/eclampsia and genetic markers related to iron status were obtained from the FinnGen Consortium and the IEU genetic databases. The “TwoSampleMR” software package in R was employed to test the genetic causality between these markers and preeclampsia/eclampsia. The inverse variance weighted (IVW) method was primarily used for MR analysis. Heterogeneity, horizontal pleiotropy, and potential outliers were evaluated for the MR analysis results.Results The random-effects IVW results showed that ferritin (OR = 1.11, 95% CI: .89–1.38, p = .341), serum iron (OR = .90, 95% CI: .75–1.09, p = .275), TIBC (OR = .98, 95% CI: .89–1.07, p = .613), and TSAT (OR = .94, 95% CI: .83–1.07, p = .354) have no genetic causal relationship with preeclampsia/eclampsia. There was no evidence of heterogeneity, horizontal pleiotropy, or possible outliers in our MR analysis (p > .05).Conclusions Our study did not detect a genetic causal relationship between iron status and preeclampsia/eclampsia. Nonetheless, this does not rule out a relationship between the two at other mechanistic levels.